A Preliminary European-Scale Assessment of Microplastics in Urban Wastewater - Obermaier, Nathan; Pistocchi, Alberto (Frontiers in Environmental Science, 2022)
Microplastics (MP) are not well defined from an analytical point of view and their measurement in the environment is still challenging. At the same time, their increasingly widespread presence is raising concerns for human health and ecosystems. In this contribution, we present a preliminary European-scale assessment of the environmental input of MP through urban wastewater and urban runoff. We quantify the emissions associated with urban wastewater based on the range of observed concentrations in wastewater treatment plants (WWTPs) effluents, and the emissions from tire wear particles (TWP) by assuming that a percentage of the particles generated on roads eventually reaches surface waters. In spite of the large uncertainties entailed in the calculation, it is apparent that TWP dominate the input of total plastic loads into European surface waters. The management of urban runoff, road runoff, and combined sewer overflows (CSO) is essential to control the emissions of MP from urban areas. On the other hand, WWTPs retain the majority of MP in the sewage sludge. The spreading of sewage sludge onto soil therefore represents a potential pathway of MP from urban wastewater into the environment.